Investigation of hybrid phosphate by complex impedance spectroscopy - Abdellatif Rafik; Elmelouky Abderrahmane; Omar Dagdag; Hansang Kim; Hafid Zouihri; Elmouloudi Sabbar; Taoufiq Guedira (Chemical Physics Impact, 2024)
In this study, we synthesized a hybrid compound, namely 4-carboxyphenylammonium dihydrogen monophosphate (C7H8O2N+.H2PO4−)[4-CADP], and successfully grew single crystals using the slow evaporation technique from an aqueous solution. Impedance measurements were conducted over a frequency range spanning 1Hz to 1MHz. Various electrical properties were systematically examined and analyzed. To the best of our knowledge, this approach has not been used before for many works carried out by spectroscopy impedance.The impedance analysis revealed that the material exhibits conductivity following Joncher's universal law with a double power law. Additionally, we conducted a thorough examination of the permittivity, modulus, and loss tangent. The atomic structure of the compound is characterized by infinite polyanions [H2PO4−]n, organized in ribbons that alternate with organic cations. The cohesion of these distinct components is facilitated by robust hydrogen bonds.